The nutritional potentials and the fatty acid profile of the seed and seed oil of Caesalpinia bonducella - Adeniyi, Adeyeye; Wasiu Kayode, Sulaiman; Olakunle Abayomi, Akinyode (International Journal of Advanced Chemistry, 2020)
The physicochemical properties of the seed and fatty acid profile of the seed oil of Caesalpinia bonducella were analyzed in this study, using standard methods of the Association of Official Analytical Chemists (AOAC). The proximate composition was found as follows: Moisture (3.24%), crude fat (41.76%), crude protein (28.63%), crude fibre (4.35%), ash content (2.94%) and carbohydrate (19.08%). The total unsaturated fatty acids (57.36%) was more abundant than the total saturated ones (42.68%). The seed oil had a high level of linoleic acid (28.15%), followed by oleic (18.41%), stearic (13.83%) and palmitic (13.56%). Other fatty acids had less than 10% each. There was a high level of unsaturation (57.36%) with oleic and linoleic acids dominating all other fatty acids with a total of 46.56%. The percentage of essential fatty acids (linoleic & linolenic acids) (32.96%) was also high at about â…“ of the total oil content. The total poly-unsaturated fatty acids (36.99%) was higher than those of mono-unsaturated (20.37%). The high level of poly-unsaturated fatty acids in the oil sample is an advantage as these are essential components of the diet of man. The good total unsaturated/saturated (or P/S) ratio of the oil, (i.e.1.344), makes it to be very nutritionally useful if adopted for domestic purposes. Â Â